2017
DOI: 10.1093/nar/gkx609
|View full text |Cite
|
Sign up to set email alerts
|

The fused SnoaL_2 domain in the Mycobacterium tuberculosis sigma factor σJ modulates promoter recognition

Abstract: Extra-cytoplasmic function (ECF) σ-factors are widespread in bacteria, linking environmental stimuli with changes in gene expression. These transcription factors span several phylogenetically distinct groups and are remarkably diverse in their activation and regulatory mechanisms. Here, we describe the structural and biochemical features of a Mycobacterium tuberculosis ECF factor σJ that suggests that the SnoaL_2 domain at the C-terminus can modulate the activity of this initiation factor in the absence of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 70 publications
3
35
0
Order By: Relevance
“…Strikingly, when mapping these co‐varying residues to the three‐dimensional structure of SigJ (PDB: 5XE7 (Goutam et al , )), we found that most of these top‐scoring predictions lie in close three‐dimensional proximity – except for the pair in σ 2 and the N‐terminus of the extension (Fig. A–C) – supporting the idea that the predicted interactions may be in physical contact.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Strikingly, when mapping these co‐varying residues to the three‐dimensional structure of SigJ (PDB: 5XE7 (Goutam et al , )), we found that most of these top‐scoring predictions lie in close three‐dimensional proximity – except for the pair in σ 2 and the N‐terminus of the extension (Fig. A–C) – supporting the idea that the predicted interactions may be in physical contact.…”
Section: Resultssupporting
confidence: 64%
“…Despite first insights into the phenomenology of σ factor control via C‐terminal extensions, the molecular mechanisms that govern this complex regulation are largely unknown. A recently described crystal structure of SigJ from Mycobacterium tuberculosis revealed that the SnoaL‐like extension might serve as a scaffold for the σ 2 and σ 4 domains in ECF41 (Goutam et al , ), potentially sequestering the σ factor into an inactive conformation. But so far, there is no structural information available for ECF groups containing other C‐terminal extensions that could help elucidating the details of their regulatory mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial studies in the ECF41 subfamily in B. lincheniformis (Firmicutes) and R. sphaeroides (α-proteobacteria) found that truncations of the NTF2 domain drastically upregulated transcription of a highly conserved promoter (12). Interestingly, biochemical and crystal structure studies of the ECF41 σ J of M. tuberculosis ( Actinobacteria ) and the ECF42 of S. venezuelae ( Actinobacteria ) revealed that the NTF2 domain was necessary for transcription (9, 10). While a direct coupling analysis of ECF41 and ECF42 revealed that the NTF2 region bind and regulate the core ECF regions of σ 2 and σ 4 responsible for transcription (11), the role of these NTF2 domains in the ECF56 subfamily has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
“…The NTF2 superfamily of domains is widely distributed on the tree of life and shows little conservation at the primary sequence identity level; but members include many enzymes and a recent review of their function has implicated allosteric regulation of DNA binding proteins (8). Studies of these NTF2 domains in ECF41 and ECF42 found it was critical to initiation of gene transcription and strongly implicate that it directly responds to an external signal (912). In 2015, a genomic survey of ECFs and other signal transduction proteins in Actinobacteria revealed another group of ECFs with similar C-terminal extensions: the ECF56 subgroup (13).…”
Section: Introductionmentioning
confidence: 99%